Partisipasi Guru dan Orang Tua Dalam Menggalakkan Literasi Pada Kalangan Pelajar - Rialdo Rezeky Manogari (Jurnal Pustaka Dianmas, 2021)
The importance of literacy for students is not just being able to read and write but more than that. Literacy is the ability to use information and knowledge to increase intelligence according to change. One method that is tried to be carried out in response to the findings in research that has occurred a lot in the phenomenon of literacy in Indonesia is to carry out Community Service in the form of discussion and knowledge dissemination entitled "Teacher and Parent Participation in Promoting Literacy Among Students" at SMPN 95 City of North Jakarta. With the aim of increasing participation from various parties, including parents, teachers and non-governmental organizations, this activity was carried out by providing contemporary examples and exposure related to the importance of literacy and community participation. Evaluation of the implementation of activities is carried out by means of socialization / counseling on materials about literacy participation.